2015
DOI: 10.1016/j.gie.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized comparison of 2 methods of cold snare polypectomy for small colorectal polyps

Abstract: NCT02036047.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
197
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(206 citation statements)
references
References 14 publications
4
197
4
1
Order By: Relevance
“…Some recent studies have shown that a dedicated snare is useful, indicating that the choice of device is also important [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown that a dedicated snare is useful, indicating that the choice of device is also important [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…From 1992 to 2016, several studies on CSP have been published . Most studies had a relatively small sample size (<300 polyps) and targeted small polyps (<10 mm in diameter).…”
Section: Discussionmentioning
confidence: 99%
“…For bowel preparation, patients followed a low‐residue diet and took 10 mL sodium picosulfate 1 day before the examination followed by 1.0 L high concentrated polyethylene glycol solution (Moviprep; Ajinomoto Pharma Co., Ltd, Tokyo, Japan) with ≥0.5 L water on the morning of the day of examination . CSP was carried out as reported previously, using three types of snare, including the Exacto cold snare (US Endoscopy, Mentor, OH, USA), Captivator II (15 mm; Boston Scientific, Marlborough, MA, USA), and Dualoop (Medico's Hirata Inc., Osaka, Japan) . In the event of immediate bleeding after resection that continued for >2 min during excision, endoscopic clipping was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from randomized trials, an increasing number of uncontrolled cohort studies suggest that cold snare polypectomy is safe and effective for up to 10 mm polyps. 46, 50, 52 …”
Section: Introductionmentioning
confidence: 99%
“…Specialized fine wire snares to facilitate cold resection have been introduced. 52, 53 A first randomized trial compared the use of a dedicated cold snare with a standard snare for cold resection of up to 10 mm polyps and found a lower incomplete resection rate with using a dedicated cold snare (9 vs. 21%). 52 …”
Section: Introductionmentioning
confidence: 99%